GROWTH AND CHARACTERIZATION OF ZnS NANOPARTICLE - Sirait, Motlan; Sirait, Makmur (JURNAL PENELITIAN SAINTIKA, 2013)
ZnS nanoparticle has been syntesized from zinc asetat andthiorea 0.2 M using copresipitation method. The structure of the ZnSnanoparticle are wurtzite with hexagonal and blende (sphalerit) withcubic shape with average size of 39.56 nm. The elements of the ZnSmeasuring using EDS it was found that Zn has a mass of sebesar52.20% with disperse energy of 8.630 keV and S element of 18.92%with disperse energy of 2.307 keV.